Anthropometric indices of late adolescents in Kopay Medical Officer of Health (MOH) area, Jaffna district - Sivakaran, M.; Arasaratnam, V.; Surenthirakumaran, R. (National Institute of Fundamental Studies, Sri Lanka, 2024)
Adolescence is a period of rapid growth and development, making adequate nutrition essential for physical, cognitive, and emotional health. The nutritional status of adolescents is a critical indicator of their overall health and development. This study aimed to determine the nutritional status of late adolescents (17-19 years) of Kopay Medical Officer of Health area, Jaffna district. A multistage cluster sampling was used. Measurements of height, weight, Mid Upper Arm Circumference (MUAC), waist circumference (WC), and hip circumference (HC) were taken. An interviewer-administered questionnaire was used to gather the socio-demographic background of the participants. Out of the total 70 adolescents, 32 were males(45.7%). The mean ages of the male and female adolescents were 17.73 (+0.8) and 18.35 (+ 0.7) years respectively. 38.6% (n=27) of adolescents were underweight and 15.8% (n=6) were overweight or obese based on the Body Mass Index (BMI) for age. Mean WC, HC and waist-hip ratio (WHR) in males and females were 72.7 (+8.8) and 72.5 (+8.2); 90.5 (+7.6); 89.9 (+6.6) and 0.8 (+0.06) and 0.8 (+0.05) respectively. Prevalence of abdominal obesity was found in 6.25% of males and 5.25% of females based on WHR and WC. Malnutrition in terms of MUAC was found in 6.3% of males and 5.3% of females. The prevalence of underweight was higher (48%) (n=13) among adolescents with family income below Rs 10,000.00. The study revealed that the prevalence of underweight and overweight among the adolescents (17-19 years) in the Kopay MOH area where the prevalence of overweight and obesity among adolescents in the study was lower compared to the prevalence of underweight. It underscores the need to encourage the frequent monitoring of the nutritional status among adolescents. The study adds region-specific knowledge to the field of adolescent nutrition regarding the dual burden of malnutrition and the socioeconomic factors influencing it.
Keywords: Body mass index; Malnutrition; Nutritionalstatus; Obesity; Underweight